Detecting financial statement audit quality factors in companies registered on the Jakarta Islamic Index (JII) period 2018-2022 - Irma, Ramadhani Irma Tripalupi; Serda, Serda Mulyasa Insani; Ade, Ade Ponirah; Sakinah, Gina (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2025)
This study aims to determine the factors that affect the quality of financial statement audits in companies listed on the Jakarta Islamic Index (JII) for the 2018-2022 period. This research uses a descriptive method with a quantitative approach. The type of data used in this study is in the form of quantitative data that is calculated directly. The data source is secondary in the form of annual financial statements published by each company listed in the Jakarta Islamic index (JII) for the 2018-2022 period. In this study, the population is companies listed in the Jakarta Islamic Index (JII) for the 2018-2022 period. There are 30 companies that make up the population in this study. The sampling method in this study used purposive sampling techniques. Then test the data using logistic regression. The results showed that the audit delay variable showed that there was no partial influence on audit quality. The audit fee shows that there is no partial influence on audit quality. Audit delay and audit fee show that there is no simultaneous effect on Audit Quality.